Demand side financing scheme for maternal and child health of Tamil Nadu: evaluation of benefit received status and awareness level among third trimester pregnant mothers, seeking care at Madurai Medical College Hospital, 2019 - Swamynathan, Meenachi; Sivasubramanian, Priya (International Journal Of Community Medicine And Public Health, 2020)
Background: Dr. Muthulakshmi Reddy Maternity Benefit Scheme (MRMBS) of Tamil Nadu Government is demand side financing scheme to poor pregnant mothers to compensate wage loss and for nutritional support. Scheme was revised during 2018. Primary objectives were to estimate proportion of benefit received status and median awareness level among third trimester pregnant mothers regarding MRMBS scheme. Secondary objective was to determine association between above two. Methods: We conducted cross sectional study among third trimester pregnant mothers who sought care at Madurai Medical College Hospital; adopted consecutive sampling; sample size 96. We collected data with semi structured questionnaire; calculated proportions with confidence intervals, median, interquartile range and performed bivariate analysis; observed privacy and confidentiality; obtained informed written consent from participants. Results: Enrollment percentage was 97% (91 to 99%). Proportion of mothers who received any benefit, any installment and any nutrition kit were 82% (72 to 89%), 39% (29 to 49%) and 76% (66 to 85%) respectively. Proportion who received appropriate benefit, appropriate instalment(s) and two nutrition kits were 3% (0.7 to 9%), 22% (14 to 31%) and 3% (0.7 to 9%) respectively. Regarding awareness score, lowest, highest, median and interquartile range were 5, 23, 14 and 11 to 17 respectively. Odds ratio for awareness score above median (exposure) and any benefit received status (outcome) was 4.2 (1.2to19.2). Conclusions: Enrollment was satisfactory. Overall any benefit received status had been achieved by at least one nutrition kit supply. Second instalment and kit issue needed improvement. Huge scope existed for improvement of awareness among beneficiaries.